2016
DOI: 10.1016/j.pnmrs.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Using NMR spectroscopy to elucidate the role of molecular motions in enzyme function

Abstract: Conformational motions play an essential role in enzyme function, often facilitating the formation of enzyme-substrate complexes and/or product release. Although considerable debate remains regarding the role of molecular motions in the conversion of enzymatic substrates to products, numerous examples have found motions to be crucial for optimization of enzyme scaffolds, effective substrate binding, and product dissociation. Conformational fluctuations are often rate-limiting to enzyme catalysis, primarily thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 130 publications
0
34
0
Order By: Relevance
“…A Bracken plot (R 1 * R 2 vs R 2 /R 1 ), which indirectly reports conformational exchange, showed that ~25 residues have significant chemical exchange or motional anisotropy, many of which belong to residues in helices α3 and α7 (Figure S1C) (Kneller et al, 2002). Over the past decades it has become clear that motions in enzymes are often coordinated with function (Boehr et al, 2006; Henzler-Wildman and Kern, 2007; Lisi and Loria, 2016; Mittermaier and Kay, 2009). Thus, these data suggest that helices α3 and α7 play key roles in PTP1B activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Bracken plot (R 1 * R 2 vs R 2 /R 1 ), which indirectly reports conformational exchange, showed that ~25 residues have significant chemical exchange or motional anisotropy, many of which belong to residues in helices α3 and α7 (Figure S1C) (Kneller et al, 2002). Over the past decades it has become clear that motions in enzymes are often coordinated with function (Boehr et al, 2006; Henzler-Wildman and Kern, 2007; Lisi and Loria, 2016; Mittermaier and Kay, 2009). Thus, these data suggest that helices α3 and α7 play key roles in PTP1B activity.…”
Section: Resultsmentioning
confidence: 99%
“…Protein dynamics are essential for protein function and regulation (Akimoto et al, 2013; Henzler-Wildman and Kern, 2007; Lisi and Loria, 2016; Masterson et al, 2010; Tzeng and Kalodimos, 2012). Most metabolic enzymes turnover quickly, and thus are highly efficient catalysts that generate large quantities of product.…”
Section: Discussionmentioning
confidence: 99%
“…These motions may be important in gating the entry and exit of substrate and products, and creating microenvironments conducive to chemical catalysis. Importantly, many of these loop motions are rate-determining [17,18,21]. Considering their functional importance, understanding and controlling active-site loop motions may be necessary in the design and engineering of next generation enzyme catalysts [26].…”
Section: Discussionmentioning
confidence: 99%
“…NMR experiments can also provide insight into the structural dynamics of proteins over a wide-range of timescales [17,18,21]. We determined R ex values (Figure 4a), the contribution of conformational exchange on the µs-ms timescale to the R 2 transverse relaxation rates.…”
Section: Severing Interactions With the C-terminal Side Of The β1α1 Lmentioning
confidence: 99%
See 1 more Smart Citation